First Episode Psychosis Services Fidelity Scale (FEPS-FS 1.0) and Manual - Addington, Donald (2021)
The First Episode Psychosis Services Fidelity Scale (FEPS-FS 1.0) is a highly reliable scale that assesses the degree to which mental health teams deliver specialized evidence-based care to people experiencing a first episode psychosis. The scale comprises 35 components each rated on a 1 to 5 scale. It has been used in the United States, Canada and Europe. It can be used for on site fidelity reviews, remote fidelity assessment or self-report. Published papers document its psychometric features and allow comparisons with a representative sample of US programs. It is suitable for research, quality improvement and accreditation. The Manual provides a practical guide for scoring a FEPS program against the criteria set out in the fidelity scale. It is designed to increase the reliability and consistency of ratings across different sites and assessors. It includes a definition and rationale for each component, data sources, decision rules and a structured interview guide. There are also modules to support training the key informant and data abstractor. Templates support structured feedback to programs for quality improvement. The scale can be adjusted to rate care for different diagnostic groups including the schizophrenia spectrum disorders, bipolar disorder and those with an attenuated psychosis syndrome.